Copper catalyst as well as preparation method, application and application method thereof

By using a functional acrylic fiber support to fix divalent copper ions in the CuAAC reaction, a stable copper catalyst is solved, and the problems of difficulty in recycling, poor stability and low catalytic efficiency of copper catalysts in the prior art are solved, and a catalytic effect that is efficient, stable and reusable is achieved.

CN119746934APending Publication Date: 2025-04-04TIANJIN UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411939068.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing copper catalysts have problems such as difficulty in recycling, poor catalyst stability, low catalytic efficiency and high functionalization in CuAAC reaction.

Method used

By heating and reflux reaction of acrylic fibers, diethylene triamine and distilled water, washing and drying, a first-stage modified acrylic fiber was obtained; then further modified with pyridine-2-formaldehyde and 1,4-dioxane, and finally mixed with divalent copper salt to form a copper catalyst, solving the stability and recovery problems of the catalyst.

Benefits of technology

The efficient catalytic activity and good stability of the copper catalyst are achieved, and the economic and practicality of the catalytic reaction is significantly improved. The catalyst still maintains an efficiency of more than 90% during multiple uses.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746934A_ABST
    Figure CN119746934A_ABST
Patent Text Reader

Abstract

The invention is suitable for the technical field of materials, and provides a copper catalyst and a preparation method, application and application method.The preparation method comprises the steps that acrylic fibers, diethylenetriamine and distilled water are mixed and then subjected to a heating reflux reaction; mixing the obtained primary modified acrylic fiber with pyridine-2-formaldehyde, 1, 4-dioxane and distilled water, and carrying out a heating reflux reaction; and carrying out water bath mixing treatment on the obtained secondary modified acrylic fiber, bivalent copper salt and distilled water at 40-60 DEG C to obtain the copper catalyst. The copper catalyst provided by the invention is a novel nitrogen heterocyclic Schiff copper (II) ligand functionalized acrylic fiber catalyst, shows excellent catalytic activity, selectivity and recoverability in a CuAAC reaction, and has a relatively good industrial application prospect; in addition, the green preparation method of the copper catalyst has the advantages of low catalyst dosage and higher catalytic efficiency, so that the copper catalyst has wide application potential in organic synthesis and chemical industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of material technology, and in particular relates to a copper catalyst and a preparation method, application and application method thereof. Background Art

[0002] Copper-catalyzed azide-alkyne cycloaddition (CuAAC) is an important "orthogonal reaction" in chemical synthesis and is widely used in drug discovery, materials science, nanotechnology and other fields. Copper (I) ions have become an important catalyst for the CuAAC reaction due to their high efficiency and selectivity. However, copper catalysts often have problems such as catalyst recovery difficulties, catalyst deactivation, and harsh reaction conditions during the synthesis process, which restricts their promotion in industrial applications.

[0003] In the existing literature, some studies have explored copper-catalyzed CuAAC reactions, most of which focus on catalyst design in solution. Although they have good catalytic activity and selectivity, they suffer from poor catalyst recovery and reusability. In addition, polymer fibers have been used as catalyst carriers for CuAAC reactions, but traditional polymer fibers usually require multiple chemical modifications to improve their catalytic performance. In addition, in the prior art, most polymer fiber catalysts have problems such as low reaction efficiency and short-term catalyst activity. In order to overcome these shortcomings, in recent years, the use of new ligands (such as Azetidic ligands) and strategies to optimize metal ion coordination have become research hotspots.

[0004] In summary, although the copper-catalyzed CuAAC reaction catalysts in the prior art have achieved certain results in some aspects, they generally have problems such as difficult recovery, poor catalyst stability, low catalytic efficiency and difficulty in functionalization. Summary of the invention

[0005] The purpose of the embodiments of the present application is to provide a method for preparing a copper catalyst, aiming to solve the problems of difficulty in recovering the catalyst for the copper-catalyzed CuAAC reaction in the prior art, poor catalyst stability, low catalytic efficiency and difficulty in functionalization.

[0006] The embodiment of the present application is implemented as follows: a method for preparing a copper catalyst comprises:

[0007] After mixing acrylic fiber, diethylenetriamine and distilled water, heating and refluxing reaction are carried out, and washing and drying are carried out to obtain primary modified acrylic fiber;

[0008] The primary modified acrylic fiber, pyridine-2-carboxaldehyde, 1,4-dioxane and distilled water are mixed, heated and refluxed, and washed and dried to obtain the secondary modified acrylic fiber;

[0009] The secondary modified acrylic fiber, divalent copper salt and distilled water are mixed in a 40-60° C. water bath and washed to obtain a copper catalyst.

[0010] The embodiment of the present application provides a copper catalyst, which is prepared by the above-mentioned method for preparing the copper catalyst.

[0011] The embodiment of the present application provides an application of the above-mentioned copper catalyst in catalyzing the CuAAC reaction.

[0012] The present application embodiment provides a method for using the above copper catalyst in catalyzing a CuAAC reaction, comprising:

[0013] A mixture of benzyl halide, terminal alkyne, sodium azide, sodium L-ascorbate, solvent and the copper catalyst of claim 8 is vigorously stirred at 40° C., and the progress of the reaction is followed by thin layer chromatography using ethyl acetate / petroleum ether as eluent; the amount of the copper catalyst is 0.05-0.3 mol%;

[0014] After the reaction is completed, the copper catalyst is separated by filtration, washed with ethyl acetate, and dried for later use; the filtrate is extracted with ethyl acetate, and the combined organic part is washed, dried, and purified to obtain the product.

[0015] The preparation method of the copper catalyst provided in the embodiment of the present application has a simple process. By combining divalent copper ions with diethylenetriamine nitrogen-containing ligands and Schiff base groups, a functionalized acrylic fiber catalyst is formed. The method can stably fix the divalent copper ions on the surface of acrylic fibers, effectively avoiding the problem of dissolution or shedding of the catalyst in traditional solution catalysis. At the same time, the method greatly enhances the reactivity, selectivity, stability, recyclability and catalytic efficiency of the copper catalyst by combining the metal complex with a polymer carrier with a high specific surface area and introducing a multifunctional specific ligand. The copper catalyst prepared in the present application not only exhibits high catalytic activity in the CuAAC reaction, but also maintains good stability and reusability in multiple reaction cycles, significantly improving the economy and practicality of the catalytic reaction. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is an EDS image of the copper catalyst provided in the examples of the present application;

[0017] Figure 2 This is a SEM image of the copper catalyst provided in the examples of the present application;

[0018] Figure 3 A hydrogen spectrum of the copper catalyst provided in the examples of the present application;

[0019] Figure 4 The carbon spectrum of the copper catalyst provided in the examples of the present application;

[0020] Figure 5 The catalytic recovery test results of the copper catalyst provided in the examples of the present application;

[0021] Figure 6 The catalytic stability test results of the copper catalyst provided in the examples of the present application. DETAILED DESCRIPTION

[0022] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0023] Although the catalysts for copper-catalyzed CuAAC reactions in the prior art have achieved certain results in some aspects, they generally have problems such as difficulty in recovery, poor catalyst stability, low catalytic efficiency, and difficulty in functionalization. The difficulty in solving these problems lies in how to design a catalytic system that can not only improve the catalytic efficiency but also ensure the recovery and stability of the catalyst. Among these difficulties, the most important challenge is how to efficiently and stably fix the copper catalyst to the polymer carrier while maintaining catalytic performance and reusability. The embodiment of the present application designs copper (II)-complexed nitrogen heterocyclic Schiff ligand functionalized Schiff base acrylic fiber as a catalyst for the CuAAC reaction, which not only effectively improves the recovery, stability and catalytic efficiency of the catalyst, but also optimizes the preparation process and selectivity of the catalyst, and solves the problems of difficulty in recovery, deactivation, low catalytic efficiency and complex functionalization of copper catalysts in the prior art. Through this innovative solution, the present application not only improves the performance of the catalyst, but also realizes the greening and efficiency of the catalyst, and provides strong technical support for the industrial application of the CuAAC reaction.

[0024] Specifically, the present invention provides a method for preparing a copper catalyst, comprising:

[0025] After mixing acrylic fiber, diethylenetriamine and distilled water, heating and reflux reaction were carried out, and then washing and drying were performed to obtain the first-level modified acrylic fiber (PAN DETA F);

[0026] The primary modified acrylic fiber, pyridine-2-carboxaldehyde, 1,4-dioxane and distilled water are mixed, heated and refluxed, washed and dried to obtain the secondary modified acrylic fiber (PAN DETA-PA F);

[0027] The secondary modified acrylic fiber, divalent copper salt and distilled water are mixed in a 40-60° C. water bath, and washed to obtain a copper catalyst (PAN DETA-PA F@Cu(Ⅱ)).

[0028] Among them, acrylic fiber (PANF) as a fiber carrier material has good mechanical strength, chemical stability and high specific surface area, can carry copper (II)-nitrogen heterocycle-Schiff base catalyst and provide sufficient active sites.

[0029] Among them, the complexes formed by pyridine ligands (such as 2,2'-bipyridine) and copper ions usually have high stability and are widely used in metal catalytic reactions. They can provide strong coordination ability and are suitable for a variety of metal catalytic reactions; imidazole ligands (such as 1-methylimidazole) can coordinate with copper ions to form stable complexes, and the imidazole group has a strong affinity for the reactant, which can improve the selectivity of the catalytic reaction. Although both pyridine and imidazole ligands can form stable complexes with copper ions, nitrogen-containing ligands have unique structural characteristics, which can improve the hydrophilicity and stability of the catalyst and show good catalytic performance for the CuAAC reaction. Therefore, the application of nitrogen-containing ligands in this application has great advantages, especially in promoting the binding of copper (II) complexes with Schiff bases. Replacing the ligands with pyridine or imidazole ligands will affect the selectivity or catalytic efficiency of the catalytic reaction.

[0030] It is worth noting that the present application significantly improves the stability and catalytic efficiency of the copper catalyst by rationally selecting a combination of aza ligands and Schiff bases; when triethylenetetramine was used as an aza ligand in the previous research, there was a problem that the copper source was less modified and insufficient to achieve the catalytic effect; and when tetraethylenepentamine and polyethylenepolyamine were used as aza ligands, there was less primary modification and the functionality was less than 0.5mmol / g. The present application embodiment selects diethylenetriamine as an aza ligand, which has a strong coordination ability, can effectively form a stable complex with copper (II) ions, and enhance the stability and activity of the catalyst.

[0031] Among them, Schiff base is an organic compound with a nitrogen atom and a carbon-nitrogen double bond, which is used as a functionalized ligand to further improve the catalytic activity and selectivity of the catalyst, preferably pyridine-2-carboxaldehyde. In some cases, an excess of Schiff base precursor may be used in the reaction to ensure a complete reaction, but this part is not necessarily necessary because the excess Schiff base may not participate in the catalytic process and may leave unreacted substances in the final product. Therefore, optimizing the amount of Schiff base precursor and controlling it within the optimal range can reduce useless waste of raw materials and improve the purity of the catalyst. Therefore, it is preferred that the number of moles of pyridine-2-carboxaldehyde is twice the mass of the fiber.

[0032] Among them, the divalent copper salt can be one or more of divalent copper sulfate, divalent copper halide, and divalent copper acetate. The choice of copper (II) salt is because it is stable during the catalytic process and is easy to form a strong complex with nitrogen-containing ligands and Schiff base functional groups. Copper (I) salts such as copper (I) chloride or copper (I) halide or copper nanoparticles may exhibit different catalytic mechanisms and reaction rates, depending on the reaction conditions. However, the copper (II) source shows better catalytic stability in the application due to its more stable characteristics. Therefore, the use of copper (II) salts is still preferred.

[0033] Among them, in the step of mixing acrylic fiber, diethylenetriamine and distilled water, heating and refluxing reaction, washing and drying to obtain primary modified acrylic fiber, the volume ratio of diethylenetriamine and distilled water is (1-2):1, and the heating and refluxing reaction time is 1-2h.

[0034] Optionally, the step of mixing acrylic fiber, diethylenetriamine and distilled water, heating and refluxing, washing and drying to obtain primary modified acrylic fiber comprises:

[0035] In a reaction apparatus equipped with a reflux condenser, 2 g of acrylic fiber, 0.05 mol of diethylenetriamine and 25 mL of distilled water were mixed, heated to reflux for 2 hours (the reflux temperature was about 130° C.) under continuous stirring, washed with water to neutrality and dried to obtain a first-grade modified acrylic fiber.

[0036] Among them, in the step of mixing the primary modified acrylic fiber, pyridine-2-carboxaldehyde, 1,4-dioxane and distilled water, heating and refluxing the mixture, washing and drying the mixture to obtain the secondary modified acrylic fiber, the volume ratio of 1,4-dioxane and distilled water is (1-2):1, and the heating and refluxing reaction time is 10-12h.

[0037] Optionally, the step of mixing the primary modified acrylic fiber, pyridine-2-carboxaldehyde, 1,4-dioxane and distilled water, heating and refluxing the mixture, and washing and drying the mixture to obtain the secondary modified acrylic fiber comprises:

[0038] 1 g of primary modified acrylic fiber, 5 mmol of pyridine-2-carboxaldehyde and 30 mL of 1,4-dioxane were mixed with 15 mL of distilled water in a reaction device equipped with a reflux condenser, and a Schiff base reaction was carried out under stirring for 10 hours (the reflux temperature was 80-100° C.), and then washed with ethanol and dried to obtain a secondary modified acrylic fiber.

[0039] Optionally, the step of mixing the secondary modified acrylic fiber, divalent copper salt and distilled water in a 40-60° C. water bath, filtering and washing to obtain a copper catalyst comprises:

[0040] 50 mL of distilled water, 1 g of secondary modified acrylic fiber and 2 mmol of divalent copper salt were added to the reaction device for mixing in a 40-60° C. water bath. The functionalized fiber was filtered out and washed with ethanol and water to obtain a copper catalyst.

[0041] The present application also provides an application of the copper catalyst in catalyzing a CuAAC reaction, and the application method thereof includes:

[0042] A mixture of benzyl halide, terminal alkyne, sodium azide, sodium L-ascorbate, solvent and the copper catalyst of claim 8 is vigorously stirred at 40° C., and the progress of the reaction is followed by thin layer chromatography using ethyl acetate / petroleum ether as eluent; the amount of the copper catalyst is 0.05-0.3 mol%;

[0043] After the reaction is completed, the copper catalyst is separated by filtration, washed with ethyl acetate, and dried for later use; the filtrate is extracted with ethyl acetate, and the combined organic part is washed, dried, and purified to obtain the product.

[0044] Alternatively, benzyl halide (0.5 mmol), terminal alkyne (0.5 mmol), sodium azide (0.6 mmol), sodium L-ascorbate (10 mol%), solvent (3 mL) and a certain amount of PAN DETA-PA A mixture of F@Cu(Ⅱ) (55 mg, 0.1 mol%) catalyst was added to a thick-walled pressure tube (10 mL). The reaction mixture was vigorously stirred at 40 °C, and the progress of the reaction was followed by thin layer chromatography (TLC) using ethyl acetate / petroleum ether as eluent. After the reaction was completed, the catalyst was separated by filtration, washed with ethyl acetate in sequence, and then dried for use. The filtrate was extracted with ethyl acetate (3×10 mL), and the combined organic portion was washed with brine (3×10 mL). The organic layer was then dried over anhydrous MgSO4. Finally, the desired product was purified by column chromatography and characterized by 1H NMR spectroscopy.

[0045] The solvent can be used to dissolve the reactants and provide a suitable reaction medium (such as water, methanol, ethanol, tetrahydrofuran, acetonitrile, etc.) to promote the reaction.

[0046] It is worth noting that the present application forms a functionalized acrylic fiber catalyst by combining copper (II) ions with nitrogen-containing ligands and Schiff base groups. The design of this copper (II)-nitrogen-containing ligand-Schiff base functionalized acrylic fiber catalyst allows copper (II) ions to be stably fixed on the fiber surface, while the introduction of ligands greatly enhances the stability, recyclability and catalytic efficiency of the catalyst. This design combines metal complexes with high-surface-area polymer carriers and increases the reactivity and selectivity of the catalyst through multifunctional ligands.

[0047] Secondly, in terms of improving the recyclability and stability of the copper catalyst, the present application effectively avoids the problem of catalyst dissolution or shedding in traditional solution catalysis by fixing the copper complex on the surface of the polyacrylonitrile fiber. This not only improves the recyclability of the catalyst, but also enhances its stability in multiple reactions. The multiple use of the catalyst will not significantly reduce the catalytic efficiency, which makes the catalytic process more efficient and economical.

[0048] Furthermore, the present application is more simplified and efficient in the process of preparing copper catalysts, and does not involve cumbersome multi-step reactions or complicated operations. For example, nitrogen-containing ligands and Schiff base functional groups can be combined with polyacrylonitrile fibers through simple chemical modification methods, and then a stable copper complex is formed through copper (II) salts. In contrast, the preparation of catalysts in the prior art often requires multiple steps and more complicated processes.

[0049] In addition, in terms of improving the catalytic efficiency of the CuAAC reaction, the present application precisely controls the binding mode of the ligand and copper (II), so that the catalyst exhibits excellent catalytic efficiency in the CuAAC reaction, especially with significant advantages in catalyst dosage and reaction time. For example, the use of the catalyst of the present application can significantly shorten the reaction time and improve the reaction conversion rate.

[0050] In addition, the present application further optimizes the activity and selectivity of the copper catalyst in terms of selectivity and adjustability of the copper catalyst by adjusting the ligand (e.g., the ratio of the nitrogen-containing ligand and the Schiff base group). This enables the catalyst to exhibit higher adaptability and efficiency for different reaction conditions and reactants.

[0051] In summary, this application involves innovations in catalyst design, material selection, and functionalization methods. Through the innovative design of using polyacrylonitrile fiber as a carrier and combining copper (II) complexes with nitrogen-containing ligands and Schiff bases, this application overcomes many deficiencies in the prior art and provides a stable, efficient, and recyclable catalyst. Its innovation is mainly reflected in the stability, recyclability, catalytic efficiency, and simplification of the preparation method of the catalyst, and these innovations are not common in the prior art, so they are not easily conceived technical alternatives.

[0052] The copper catalyst of the present application and its preparation method, application and application method are described in detail with specific examples as follows. The experimental methods used in the following examples are conventional methods unless otherwise specified; the materials, reagents, etc. used are all commercially available unless otherwise specified.

[0053] Example 1: Preparation of copper catalyst

[0054] (1) PAN DETA Primary modification of F

[0055] In a 100 mL round bottom flask equipped with a reflux condenser, dry PANF (2.00 g) and diethylenetriamine (0.05 mol) were mixed with distilled water (25 mL). The reaction mixture was heated to reflux for 2 h under continuous magnetic stirring. After the reaction was complete, the fiber was filtered and washed with water (70 °C) until the wash water was neutral. The resulting PAN was then DETA F was dried in an oven at 60°C until it reached a constant weight, and the weight increased by 20.1% (f = 1.61 mmol / g) based on PANF.

[0056] (2) PAN DETA-PA Secondary modification of F

[0057] The dried PAN DETA F (1.00 g), pyridine-2-carboxaldehyde (5 mmol) and 1,4-dioxane (30 mL) were mixed with distilled water (15 mL) in a 100 mL round-bottom flask equipped with a reflux condenser. The Schiff base reaction was carried out under magnetic stirring for 10 h. After the reaction was completed, the fiber was carefully picked up with tweezers, and then washed with ethanol as the extraction solvent in a Soxhlet extractor for 12 h and dried to obtain PAN. DETA-PA F.

[0058] (3) PAN DETA-PA Metal Complexation of F@Cu(Ⅱ)

[0059] In a 100 mL round-bottom flask, add distilled water (50 mL) and dry PAN DETA-PA F (1.00 g) and Cu(OAc)2 (2 mmol) were mixed in a 50°C water bath. The functionalized fibers were then filtered out and washed with ethanol and distilled water to obtain PAN. DETA-PA F@Cu(Ⅱ). The copper (Cu) content was quantified using ICP-AES, and the result was 0.91 mmol / g.

[0060] (4) Determination of functionalized fiber loading

[0061] The degree of modification of the fibers was quantified by two parameters: weight gain (w, %) and functionality (f, mmol / g).

[0062] The formula for calculating the weight gain w is w = (m-m0) / m×100%. Where m is the modified fiber (i.e. PAN DETA F or PAN DETA-PA F), m0 is the weight of the original PANF.

[0063] The functionality f depends on the increase in molecular weight after fiber modification, and its calculation formula is f = w / (1+w)×M×1000, where M refers to the molar mass of the aminating agent (i.e., diethylenetriamine, M=103.17) and pyridine-2-carboxaldehyde (M=107.11) in the two modification processes, respectively.

[0064] The copper catalyst PAN obtained in the above example DETA-PA F@Cu(Ⅱ) was subjected to EDS and SEM tests.

[0065] Among them, the EDS test results are as follows Figure 1 As shown in the figure, the elemental analysis results show that the carbon, nitrogen and oxygen elements in acrylic fiber correspond to Figure 1 (a) Figure 1 (b) and Figure 1 (c) Figure 1 (d) represents the loaded copper element. The successful detection of the copper element indicates that the metallic copper has been effectively loaded on the fiber surface, thus proving the successful preparation of the functionalized fiber catalyst. This result further supports the effectiveness of the complexation reaction and the excellent loading capacity of the fiber surface for metal ions.

[0066] SEM test results are as follows Figure 2 As shown in the figure, it can be seen that the surface of PANF is relatively smooth, and there is no obvious morphological structure in the organic component. When copper acetate is used as the copper source, the imine bond complexed with divalent copper is attached to PAN DETA-PAThe surface of F@Cu(II) forms Schiff base-copper complex particles of uniform size. Specifically, at a magnification of 200μm, the surface of the functional fiber exhibits a relatively smooth structural feature, indicating that the fiber surface maintains a high degree of integrity and uniformity after treatment. At a resolution of 20μm, it can be clearly observed that the metallic copper is uniformly loaded on the fiber surface, and there is no obvious breakage or structural damage on the surface, indicating that the loading process did not cause excessive physical damage or degradation to the fiber. When further magnified to 2μm, the distribution of the complexed copper appeared more uniform, and no aggregation or clustering of copper particles was found, indicating that the complexation reaction of copper ions on the fiber surface was effectively controlled, thereby ensuring the uniform distribution of catalytic active sites. These observations indicate that the functional fiber exhibits good stability and uniform surface properties during the process of loading metallic copper.

[0067] Example 2: Application of copper catalyst in CuAAC reaction

[0068] The synthetic route of the azide and alkyne cyclization product 4a is as follows:

[0069]

[0070] Benzyl bromide 2a (0.5 mmol), phenylacetylene 1a (0.5 mmol), sodium azide 3 (0.6 mmol), sodium L-ascorbate (10 mol%), water (3 mL) and PAN prepared in Example 1 were added. DETA-PA A mixture of F@Cu(Ⅱ) (55 mg, 0.1 mol%) catalyst was added to a thick-walled pressure tube (10 mL). The reaction mixture was vigorously stirred at 40 °C, and the progress of the reaction was tracked by thin layer chromatography (TLC) using ethyl acetate / petroleum ether as eluent. After the reaction was completed, the catalyst was separated by filtration, washed with ethyl acetate in sequence, and then dried for use. The filtrate was extracted with ethyl acetate (3×10 mL), and the combined organic portion was washed with brine (3×10 mL). The organic layer was then dried over anhydrous MgSO4. Finally, the desired product 4a was purified by column chromatography and purified by 1 HNMR spectroscopy and 400M NMR were used to characterize it. The characterization results are as follows Figure 3-4 shown.

[0071] 1-Benzyl-4-phenyl-1H-1,2,3-triazole (4a), white solid, melting point: 131.8-132.5℃

[0072] 1H NMR (400MHz, DMSO-d6) δ8.64(s,1H),7.85(d,J=7.6Hz,2H),7.50–7.37(m,4H),7.37–7.15(m,4H),5.65(s,2H).13C NMR (101MHz, DMSO-d6) δ147.14,136.49,131.14,129.37,129.28,128.64,128.36,125.63,122.04,53.50.

[0073] The recovery test results of the above copper catalyst are as follows: Figure 5 As shown in the figure, in the CuAAC reaction, the catalyst has a high catalytic efficiency. The reaction time is 5 hours. After the catalyst is recycled 10 times, the catalytic efficiency remains above 90%. Under the conditions of multiple reactions, the stability of the catalyst has been verified, such as Figure 6 As shown, after 10 consecutive CuAAC reactions, the fracture strength of the catalyst only decreased by less than 10%, still maintaining at 62%. In addition, the experimental results show that when the copper catalyst of the present application is used, the reaction time of the CuAAC reaction is greatly shortened. At 40°C, the copper catalyst of the present application can complete the reaction within 5 hours, while the traditional catalyst requires more than 10 hours.

[0074] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.

[0075] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A method for preparing a copper catalyst, characterized in that: include: After mixing acrylic fiber, diethylenetriamine and distilled water, heating and refluxing reaction are carried out, and washing and drying are carried out to obtain primary modified acrylic fiber; The primary modified acrylic fiber, pyridine-2-carboxaldehyde, 1,4-dioxane and distilled water are mixed, heated and refluxed, and washed and dried to obtain the secondary modified acrylic fiber; The secondary modified acrylic fiber, divalent copper salt and distilled water are mixed in a 40-60° C. water bath and washed to obtain a copper catalyst.

2. The method for preparing a copper catalyst according to claim 1, characterized in that: The divalent copper salt is one or more of divalent copper sulfate, divalent copper halide, and divalent copper acetate.

3. The method for preparing a copper catalyst according to claim 1, characterized in that: In the step of mixing acrylic fiber, diethylenetriamine and distilled water, heating and refluxing, washing and drying to obtain primary modified acrylic fiber, the volume ratio of diethylenetriamine and distilled water is (1-2):1, and the heating and refluxing reaction time is 1-2h.

4. The method for preparing a copper catalyst according to claim 1, characterized in that: In the step of mixing the primary modified acrylic fiber, pyridine-2-carboxaldehyde, 1,4-dioxane and distilled water, heating and refluxing the mixture, washing and drying the mixture to obtain the secondary modified acrylic fiber, the volume ratio of 1,4-dioxane and distilled water is (1-2):1, and the heating and refluxing reaction time is 10-12h.

5. The method for preparing a copper catalyst according to claim 1, characterized in that: The step of mixing acrylic fiber, diethylenetriamine and distilled water, heating and refluxing, washing and drying to obtain primary modified acrylic fiber comprises: In a reaction apparatus equipped with a reflux condenser, 2 g of acrylic fiber, 0.05 mol of diethylenetriamine and 25 mL of distilled water were mixed, heated to reflux for 2 hours under continuous stirring, washed with water to neutrality and dried to obtain a first-grade modified acrylic fiber.

6. The method for preparing a copper catalyst according to claim 1, characterized in that: The step of mixing the primary modified acrylic fiber, pyridine-2-carboxaldehyde, 1,4-dioxane and distilled water, heating and refluxing the mixture, washing and drying the mixture to obtain the secondary modified acrylic fiber comprises: 1 g of primary modified acrylic fiber, 5 mmol of pyridine-2-carboxaldehyde, 30 mL of 1,4-dioxane and 15 mL of distilled water were mixed in a reaction device equipped with a reflux condenser, and a Schiff base reaction was carried out for 10 hours under stirring. The secondary modified acrylic fiber was obtained by washing with ethanol and drying.

7. The method for preparing a copper catalyst according to claim 1, characterized in that: The step of mixing the secondary modified acrylic fiber, divalent copper salt and distilled water in a 40-60° C. water bath, filtering and washing to obtain a copper catalyst comprises: 50 mL of distilled water, 1 g of secondary modified acrylic fiber and 2 mmol of divalent copper salt were added to the reaction device for mixing in a 40-60° C. water bath. The functionalized fiber was filtered out and washed with ethanol and water to obtain a copper catalyst.

8. A copper catalyst, characterized in that The copper catalyst is prepared by the method for preparing the copper catalyst according to any one of claims 1-7.

9. Use of the copper catalyst according to claim 8 in catalyzing CuAAC reaction.

10. A method for using the copper catalyst according to claim 8 in catalyzing a CuAAC reaction, characterized in that: include: A mixture of benzyl halide, terminal alkyne, sodium azide, sodium L-ascorbate, solvent and the copper catalyst of claim 8 is vigorously stirred at 40° C., and the progress of the reaction is followed by thin layer chromatography using ethyl acetate / petroleum ether as eluent; the amount of the copper catalyst is 0.05-0.3 mol%; After the reaction is completed, the copper catalyst is separated by filtration, washed with ethyl acetate, and dried for later use; The filtrate was extracted with ethyl acetate, and the combined organic fractions were washed, dried, and purified to obtain the product.

Citation Information

Patent Citations

  • Preparation method and application of Schiff base functionalized ordered mesoporous PMO material solid supported Cu(I) heterogeneous catalyst

    CN101879459A

  • Method for preparing amylose-loaded copper-based catalyst and product thereof and applications of product

    CN108940371A

  • Polyacrylonitrile-based-diethylenetriamine chromogenic fiber and synthesis method and application thereof

    CN111851063A